THE INFLUENCE OF BRAND IMAGE AND PRICES TOWARDS TOOTHPASTE PURCHASE DECISIONS AT MEMBERS OF PT. NATURAL NUSANTARA - Nur Laelatun Nisa; Nurminingsih Nurminingsih (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to analyze and explain the influence of brand image and price on purchasing decisions of NASA toothpaste at members of PT. Natural Nusantara. The existence of a good brand image certainly has an impact on affordable prices and in accordance with the benefits that affect the purchase decision of a product that consumers will be interested in. This type of research uses quantitative methods, the sampling technique is random sampling, data collection is to spread questionnaires using Google form, collect data from all elements in the population, namely members of PT. Natural Nusantara. The number of samples is 73 respondents. The questionnaire is the main instrument for collecting primary data. Research analysis using SEM-PLS. The findings of this study reveal that brand image has a positive and significant influence on purchasing decisions, while prices have a positive and significant influence on purchasing decisions, and brand image has a positive and significant influence on prices. Based on this research, it can be concluded that this research hypothesis is accepted.